BRIEFING NOTE ABOUT ACTIVITY OF EDITORIAL BOARD OF “RATIONAL PHARMACOTHERAPY IN CARDIOLOGY” IN 2009 (Рациональная фармакотерапия в кардиологии, 2016)
Briefing note about activity of editorial board of “Rational Pharmacotherapy in Cardiology” in 2009.